Deformations in trapdoor tests and piled embankments. Issue 2 (17th June 2019) - Rui, R.; Zhai, Y. X.; Han, J.; van Eekelen, S. J. M.; Chen, C.
Abstract : Fill deformation and surface settlement can be induced by differential settlement at the bottom of the fill in piled embankments. The deformation patterns and the relationship between the surface settlement and the differential settlement at the bottom of the fill have not been well investigated. Two-dimensional single-trapdoor, twin-trapdoor, and multi-trapdoor tests, including four tests with geosynthetic reinforcement, were conducted using elliptical steel rods as an analog to soil. The deformation pattern and influence regions in the single-trapdoor tests were evaluated using the measured deformations. The fill deformations in the trapdoor tests followed the Gaussian distribution. The superposition results of these Gaussian distribution curves of the single-trapdoor tests were compared with the measured deformations in the twin-trapdoor and multi-trapdoor tests. The differences between the measured and calculated results indicate that additional interaction occurred between adjacent trapdoors. The deformation shapes of the fill at the bottom of the geosynthetic-reinforced and unreinforced test sections were different. However, the settlement pattern at the elevation level above 1.5 times the clear spacing of pile caps followed the same Gaussian distribution curve, if the volumetric settlement was the same. A method for predicting the surface settlement of 2D piled embankments is then presented.